The results of the international clinical study VICTORY:efficacy and safety of antihypertensive monotherapy with valsartan (Valsacor®) and its fixed combination with hydrochlorothiazide(Valsacor® H)in routine clinical practice in patients with hypertens - Chazova I.E.; Martynyuk T.V.; Accetto R. (Системные гипертензии, 2017)
Objective. The VICTORY study aimed to evaluate effectiveness and safety of monotherapy with valsartan (Valsacor®) and its fixed combination with hydrochlorothiazide (Valsacor® H) in clinical practice in patients with stage 1 and stage 2 hypertension. Materials and methods. In the prospective, randomized, open-label, international multicentre study involved 356 patients with grade 1 and grade 2 hypertension from 5 countries, including 130 patients from Russia. In Russia the study was conducted in 7 cities, in 8 clinical centers. The patients, who were receiving antihypertensive therapy at the moment of screening, underwent a 7 days wash-out period. The starter dose of valsartan (Valsacor®, KRKA, Slovenia) was 80 mg (except for Russia where 160 mg of Valsacor® were given at the first visit, what did not influence the study results). After 4 weeks of treatment in case of blood pressure (BP) >140/90 or 130/80 mm Hg the dose was increased to 160 mg (in Russia – to 320 mg) or combined therapy with Valsacor® H (KRKA, Slovenia) was prescribed. In 4 weeks the dose of valsartan was increased to 320 or 160/12.5 mg in case of previous dose insufficiency. If target BP levels were not reached in the next 4 weeks, the dose was increased to 320/12.5 mg. The primary endpoints included evaluation of antihypertensive effect of valsartan and its fixed combination with hydrochlorothiazide on BP levels; evaluation of the drugs’ influence on aortal stiffness; comparison of absolute average means of achieved decrease in central and peripheral BP compared with baseline; evaluation of the impact on aortic augmentation index. The secondary endpoints included comparison of primary endpoints when using mono and combined therapy; evaluation and comparison of the effect on erectile function in men by questionnaires at baseline and after 16 weeks of treatment; evaluation of adverse events frequency. Results. Data on 365 patients – 196 (54.0%) female and 169 (46.0%) male aged 54.6±12.0 years were analyzed. Mean initial value of systolic (SBP) and diastolic BP (DBP) were 156.6±8.9 and 95.6±6.0 mm Hg, respectively and 130.1±8.2 and 80.9±5.8 mm Hg, respectively after 16 weeks of treatment. The mean absolute decrease of SBP and DBP was 26.6±10.4 and 14.8±7.6 mm Hg. The decrease of SBP and DBP was statistically significant in all treatment periods (р<0,0001). The mean absolute decrease of central SBP and DBP at the 5th visit was 19.7±12.9 and 13.9±8.5 mm Hg, respectively (р<0.0001). When compared, the mean values of SBP and DBP between groups of mono and combined therapy were statistically significant (р<0.0001). 90,6% of patients reached the target BP levels: 98% in those who received monotherapy with valsartan and 84% in those who received combination of valsartan and hydrochlorothiazide. The mean absolute increase of erectile function score was 0.84±2.45 (p<0.0001). There were no differences in erectile function score dynamics in the two groups of patients. 92.8% of patients did not experience adverse effects and adverse events associated with the medication. There were no cases of severe adverse events in the study. The most frequent adverse effects were headache (1.9%), dizziness (1.6%), and weakness (1.6%). Conclusion. The study demonstrated high effectiveness and good tolerability of valsartan and its fixed combination with hydrochlorothiazide (Valsacor®, Valsacor® H) in patients with stage 1 and stage 2 hypertension. 1. Valsartan in monotherapy (Valsacor®) and in combination with hydrochlorothiazide (Valsacor® H) lowers the SBP and DBP levels to reference levels. 2. At the 16th week of treatment 90.6% reached target BP levels: 98% in the valsartan monotherapy group and 84% in the combination therapy with valsartan and hydrochlorothiazide group. 3. The medications Valsacor® and Valsacor® H have good tolerability: 92.8% of the patients did not experience any adverse effects. 7.1% of patients had at least 1 adverse effect but none of them experienced any severe adverse events. 4. The therapeutic effect was estimated as good and very good in 96.9% of patients. 5. The overall clinical effectiveness was estimated as excellent, very good and good in 95.3% of patients. 6. Most of the patients receiving Valsacor® and Valsacor® H noted an increase in life quality. 7. Treatment with Valsacor® and Valsacor® H resulted in increase of erectile function in male patients with stage 1 and stage 2 hypertension.